Synthesis and evaluation of flexible pyrimethamine analogues as antifolates against drug-resistant malaria - Maree, Matthew (University of the Witwatersrand, Johannesburg, 2025)
In many parts of the world today, malaria still represents a major health crisis, with millions of cases and hundreds of thousands of deaths reported each year. The major malaria causing parasite is Plasmodium falciparum, which accounts for the majority of cases and deaths worldwide. This parasite has shown a remarkable ability to rapidly mutate and develop resistance against initially effective drug molecules. The continued threat of malaria today motivates the development of new molecules which can remain active despite point mutations that arise in the active site of the targeted enzymes. Previous work done by A. Rousseau and colleagues showed that modifying existing class II antifolates, which target the bifunctional parasite enzyme dihydrofolate reductase – thymidylate synthase (DHFR-TS), by adding a flexible four-atom linker allowed for high levels of antiplasmodial activity to be maintained against drug-resistant forms of the parasite. In the present work, molecular modelling techniques were used to optimize the structural elements of flexible pyrimethamine analogues for binding ability against mutant enzymes. The effects of various functional groups around a conserved structure were evaluated, and a library of compounds was selected for synthesis. Numerous flexible pyrimethamine analogues were successfully synthesized making use of partially established experimental procedures, and were submitted for various antiplasmodial assessments. The synthesized compounds showed excellent activity in single enzyme assays, inhibiting drug-resistant PfDHFR enzymes at low nanomolar concentrations. Whole cell assays were also conducted, where a significant decrease in activity was observed, with the most active compounds inhibiting the parasite cells at low micromolar concentrations. These results suggested that while the compounds were effective binders of the target enzyme, they had some pharmacokinetic limitations which prevented them from effectively exhibiting their mode of action inside the cell. A second-generation of analogues was then envisaged, taking inspiration from existing antifolate compounds which are known to have favourable pharmacokinetic properties. Methods for the synthesis of the devised second-generation analogues were developed as part of this work, and the binding ability of the compounds was validated with further molecular modelling studies. We are currently awaiting the results for the biological assessments of the second-generation analogues.
Thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2025
Keywords: Malaria; Organic synthesis; Molecular modelling; Drug development; UCTD; SDG-3: Good health and well-being; SDG-9: Industry, innovation and infrastructure